Empowerment Partnership Public Group Business in Tebet District, South Jakarta City - Dewi Wuisan; Napitupulu, Joshua Fernando; Herlina Lusmeida (Universitas Pelita Harapan, 2024)
The potential of cassava as a staple food in Indonesia, although not fully utilised. Innovation in processing cassava into chips is a solution to increase cassava consumption and overcome nutritional problems such as stunting. Through the